Solid-Phase Extraction of Polybrominated Diphenyl Ethers in Human Plasma ? Comparison with an Open Column Extraction Method - Karlsson, M.; Julander, A.; van Bavel, B.; Lindstr m, G. (Chromatographia, 2005)
A solid phase extraction (SPE) method in combination with silica gel cleanup to analyse tri-to heptabrominated diphenyl ethers in human plasma was validated. All congeners showed recoveries over 70% except for BDE #183, which showed recoveries around 45%. The method was tested on 21 individual plasma samples which were extracted with both the SPE method and an open column extraction method using Hydromatrix. Method detection limits were of the same order of magnitude for both methods, ranging from 0.0076 to 0.13 ng g −1 (l.w.) depending on the congener. The SPE extraction method meets the demand for a faster, less solvent-and sample-demanding method with lower contamination risk due to fewer steps compared to the open column extraction.